Current issues in databases and information systems : East-European Conference on Advances in Databases and Information Systems held jointly with International Conference on Database Systems for Advanced Applications, ADBIS-DASFAA 2000, Prague, Czech Republic, September 5-9, 2000, proceedings - Stuller, Julius; Pokorny, Jaroslav; Thalheim, Bernhard; Masunaga, Yoshifumi (Lecture notes in computer science ;, 2000)
This volume presents the refereed proceedings of the East-European Conference on Advances in Databases and Information Systems and of the International Conference on Database Systems for Advanced Applications, ADBIS-DASFAA 2000, held jointly in Prague, Czech Republic in September 2000. The 27 revised papers presented together with one invited paper and the abstract of an invited talk were carefully reviewed and selected from 115 submissions. The papers present new results on a variety of current issues in database research and design with a certain emphasis on advanced applications in various fields.